Mortality from early onset group B streptococcal infection in the United Kingdom. Issue 2 (1st March 1999) - Embleton, Nick; Wariyar, Unni; Hey, Edmund
Abstract : AIMS: To assess the assumption that group B streptococcal infection is less common in the United Kingdom than it is in the United States. METHODS: All stillbirth and neonatal death records in the former Northern Health Region were scrutinised to determine how many babies had died of infection in 1981–96, and what had been the cause. RESULTS: Fifty one of 630 206 live born babies had died of confirmed group B streptococcal infection after becoming symptomatic within 48 hours of birth (0.8 neonatal deaths per 10 000 live births). There were a further 27 deaths from infection without a confirmed microbiological diagnosis, and 17 stillbirths from confirmed group B streptococcal infection. CONCLUSIONS: The incidence of death from early onset infection was marginally higher than the officially estimated rate for the United States before widespread prophylaxis was attempted. Strategies for perinatal prevention deserve greater attention in the United Kingdom.